Numerical experiments in plasma focus operated in various gases - Akel, M.; Lee, S.; Saw, S. H. (IEEE, 2012)
We adapted the Lee Model code as a branch version RADPF5.15K to gases of special interest to us, namely, nitrogen and oxygen and applied numerical experiments specifically to our AECS PF-1 and AECS PF-2. We also generalized the numerical experiments to other machines and other gases to look at scaling laws and to explore recently uncovered insights and concepts. The required thermodynamic data of nitrogen, oxygen, neon, and argon gases (ion fraction, the effective ionic charge number, the effective specific heat ratio) were calculated, the X-ray emission properties of plasmas were studied, and suitable temperature range (window) for generating H- and He-like ions (therefore soft X-ray emissions) of different species of plasmas were found. The code is applied to characterize the AECS-PF-1 and AECS-PF-2, and for optimizing the nitrogen, oxygen, neon, and argon SXR yields. In numerical experiments we show that it is useful to reduce static inductance L0 to a range of 15-25 nH; but not any smaller. These yields at diverse wavelength ranges are large enough to be of interest for applications. Scaling laws for argon and nitrogen SXR were found. Model parameters are determined by fitting computed with measured current waveforms in neon for INTI PF and in argon for the AECS PF-2. Radiative cooling effects are studied indicating that radiative collapse may be observed for heavy noble gases (Ar, Kr, Xe) for pinch currents even below 100 kA. The creation of the consequential extreme conditions of density and pulsed power is of interest for research and applications.